Effect of Green Apple Juice on SOD And IL-6 in Cigarette Smoked Rats - Chandra Pranata; Asti Pratiwi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Cigarette smoke contains oxidants or free radicals and approximately 4,700 hazardous chemicals. Elevated levels of free radicals in the body can trigger the generation of Reactive Oxygen Species (ROS), leading to oxidative stress. This condition arises when there is an imbalance between oxidants and antioxidants. During this process, oxygen (O2) leakage occurs, resulting in the formation of superoxide radicals (*O2), which can subsequently induce the production of pro-inflammatory cytokines such as IL-6. The objective of this study was to evaluate the effect of green apple juice supplementation on superoxide dismutase (SOD) and IL-6 levels in male Wistar rats exposed to cigarette smoke. The study employed a Post-Test Only Control Group Design. A total of 20 male rats that met the inclusion criteria were randomly assigned to four groups: K1, K2, K3, and K4. Group K3 received standard feed supplemented with green apple juice at a dose of 13.5 grams per day, while group K4 received standard feed supplemented with green apple juice at a dose of 27 grams per day. Both groups were exposed to cigarette smoke for 14 consecutive days. On the 15th day, blood samples were collected from the male Wistar rats to measure SOD and IL-6 levels using the ELISA method. Data were analyzed using a One-Way ANOVA test, followed by Tukey's Post Hoc test. The results showed that the highest average SOD level was observed in group K2 (1.76 ng/L), while the highest IL-6 level was recorded in group K1 (4.08 ng/L). The One-Way ANOVA test indicated significant differences in SOD and IL-6 levels among the groups, with a p-value of <0.05.